APLIKASI LAUNDRY BERBASIS WEBSITE MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT (RAD) PADA LC JAYA CLEAN - Ali Mansyur H, Sidik; Dwicahya Supriatman, Rian; Mulyana, Dadan (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2024)
In the digital era, information technology is crucial for daily activities, enhancing efficiency and effectiveness. This transformation is evident in the business sector, where digitalization boosts data accuracy, reduces human error, and improves productivity and quality. For busy societies, laundry services like Lc Jaya Clean provide practical solutions for washing and caring for clothes. Utilizing a web-based laundry application system and the Rapid Application Development (RAD) method, Lc Jaya Clean enhances data management, customer interaction, and service flexibility. The study employs the RAD method, comprising requirements planning, system design, and implementation stages, facilitating quick prototyping, iterative testing, and user feedback. The successful development of the web- based laundry application used the Laravel framework and PHP, with Visual Studio Code, XAMPP, Figma, StarUML, and Draw.io for coding and design. The RAD process and user feedback produced a user-friendly, tailored application, improving data management and business processes for Lc Jaya Clean.